(untitled) (International journal of artificial intelligence, 2026)
The process of prototyping for the effective selection of innovative ideas and their implementation ensures innovative efficiency. The article proposes a systematic methodology for sorting, evaluating and creating prototypes of conceptual innovative ideas in engineering projects. This methodology is associated with theoretical foundations, evaluation criteria and practical tools, and ensures the reduction of project risks and optimal use of resources. In modern engineering practice, the effective integration of scientific and innovative ideas into production and technological processes is of strategic importance. This article analyzes the main methods of integrating scientific and innovative ideas into engineering processes, mechanisms for technological improvement, and ways to increase their efficiency.